Genetic Improvement of Japonica Rice Variety Wuyujing 3 for Stripe Disease Resistance and Eating Quality by Pyramiding Stv-bi and Wx-mq - Tao, Chen; Hao, Wu; Ya-dong, Zhang; Zhen, Zhu; Qi-yong, Zhao; Li-hui, Zhou; Shu, Yao; Ling, Zhao; Xin, Yu; Chun-fang, Zhao; Cai-lin, Wang (Rice science, 2016)
Japonica rice variety Kanto 194 as the donor of resistance gene Stv-b^i and Iow-amylose content gene Wx-mq was used to improve the resistance and eating quality of Wuyujing 3 by the breeding strategy of backcross. In continuous backcross and selfcross generations, the related molecular markers with Stvobi and Wx-mq genes were utilized for genotypic detection by associated with resistance identification of rice stripe disease and agronomic traits selection. Finally, 10 improved lines with homozygous genotype Stv-b^i Stv-b^iWx-mqWx-mq were obtained from BC3F4 generation. The results of comparative analysis indicated that most characters of these lines were consistent with those of recipient parent Wuyujing 3, except for the improved resistance, appearance and eating quality. By evaluation of the comprehensive performance of them, two excellent lines K01 and K04 were selected for further experiments.